2020
DOI: 10.1183/13993003.00337-2020
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and rheumatoid arthritis associated interstitial lung disease

Abstract: Question addressed by the studyMethotrexate (MTX) is a key anchor drug for rheumatoid arthritis (RA) management. Fibrotic interstitial lung disease (ILD) is a common complication of RA. Whether MTX exposure increases the risk of ILD in patients with RA is disputed. We aimed to evaluate the association of prior MTX use with development of RA-ILD.MethodsThrough a case-control study design with discovery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(99 citation statements)
references
References 42 publications
3
83
0
13
Order By: Relevance
“…Extended analysis, showed MTX exposure was associated with a reduced risk of developing incident ILD [Odds Ratio (OR) 0.48 P = 0.004] and longer time to ILD diagnosis (OR 0.41 P = 0.004). Juge et al [ 30 ] undertook a case–control study in 410 patients with HRCT diagnosed with fibrotic RA-ILD and 673 patients with RA without ILD on HRCT. The combined estimate revealed an adjusted OR of 0.43 (95% CI 0.26–0.69; P = 0.0006) in MTX ever users for ILD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extended analysis, showed MTX exposure was associated with a reduced risk of developing incident ILD [Odds Ratio (OR) 0.48 P = 0.004] and longer time to ILD diagnosis (OR 0.41 P = 0.004). Juge et al [ 30 ] undertook a case–control study in 410 patients with HRCT diagnosed with fibrotic RA-ILD and 673 patients with RA without ILD on HRCT. The combined estimate revealed an adjusted OR of 0.43 (95% CI 0.26–0.69; P = 0.0006) in MTX ever users for ILD.…”
Section: Resultsmentioning
confidence: 99%
“…This may have led to the clinical picture becoming muddled in some cases. Two recent studies have shown MTX reduces the risk of developing fILD, delaying its onset [ 29 , 30 ] and one found MTX treatment was clinically and statistically associated with improved survival [ 28 ]. These findings are very much against MTX causing or exacerbating ILD in patients with RA and in fact may indicate some sort of protective mechanism afforded by use of MTX at least in RA f ILD cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of immunosuppressive agents in RA-UIP remains unclear, and patients with inflammatory types of ILD, such as NSIP and organizing pneumonia, generally have a better response to immunosuppressive agents. There are historical concerns about methotrexate (MTX)-related hypersensitivity pneumonitis and the association between MTX and RA-ILD, but in a recent study by Juge et al, MTX was not associated with an increased risk of RA-ILD, and ILD detection was delayed by 3.6 years [ 55 ].…”
Section: Immunosuppressive Treatment: Where Are We?mentioning
confidence: 99%
“…16,17 Recent studies indicate that treatment with methotrexate does not increase the risk of chronic ILD in RA. [18][19][20]…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Recent studies indicate that treatment with methotrexate does not increase the risk of chronic ILD in RA. 18 20 The pathogenesis of AoDILD is believed to involve “immune reconstitution inflammatory syndrome” caused by infection by pathogens including Pneumocystis jirovecii . 21 Patients with collagen disease treated with immunosuppressive drugs may be affected by immune reconstitution inflammatory syndrome.…”
Section: Introductionmentioning
confidence: 99%